Deterministic Seismic Hazard Analysis to Determine Liquefaction Potential Due to Earthquake - K. A. Hanindya; Lalu Makrup; . Widodo; R. Paulus (Civil Engineering Journal, 2023)
The great rocking of building structures and the occurrence of liquefaction in water-saturated soil on river banks are generally caused by earthquake shaking. The waves generated by the earthquake are the main cause of the shaking. In order to show the effect of ground motion earthquake shaking on the response of structures and liquefaction processes, it is necessary to analyze the structure and liquefaction as well as the time history of artificial earthquake ground motions. An artificial time history for liquefaction analysis can be developed based on spectral matching to the target spectrum generated by a deterministic seismic hazard analysis. Therefore, the time history recovered from the analysis can be said to be derived from a deterministic procedure. The analysis of liquefaction with time history aims to see the potential for liquefaction in the Palu region of Central Sulawesi by developing the time history of the bedrock. The time history of the bedrock is then spread over the ground surface. The propagation of time-historical waves to the ground surface can cause liquefaction events in the soil layer. It was found that liquefaction occurred in the Palu region, especially in the Anutapura Hospital building. No other liquefaction potential analysis studies were found in the region. Doi: 10.28991/CEJ-2023-09-05-012 Full Text: PDF